Clinic‐level differences in human papillomavirus vaccination rates among rural and urban Oregon primary care clinics. Issue 2 (17th November 2022) - Hatch, Brigit A.; Valenzuela, Steele; Darden, Paul M.; Fagnan, Lyle J.; Dickinson, Caitlin; Marino, Miguel; Robison, Steve G.; Larsen, Rex; Carney, Patricia A.
Abstract: Purpose: Human papillomavirus (HPV) infection contributes to vaccine‐preventable malignancies. Rural populations experience lower HPV vaccination rates despite similar rates of other childhood vaccinations. Individual‐ and clinic‐level characteristics likely contribute to this disparity, but little is known about the separate roles of each. We compared clinic‐level HPV vaccination rates among rural versus urban primary care clinics, identified factors associated with HPV vaccination, and separately assessed the impact of individual‐ and clinic‐level characteristics on rural disparities in HPV vaccination. Methods: This cross‐sectional study included 537 Oregon primary care clinics participating in the Vaccines for Children (VFC) program during 2019. Vaccination status was assessed using Oregon's ALERT Immunization Information System and included HPV vaccine ≥ 1 dose for ages 11 and 12; HPV vaccination up to date (UTD) for ages 13‐17, and coadministration with tetanus, diphtheria, and acellular pertussis (Tdap). Rural versus urban clinic‐level outcomes were assessed using negative binomial regression. Findings: Participating clinics were 24.5% rural and 75.6% urban. Family medicine clinics comprised 71.1%; pediatrics, 16.9%; and mixed, 12.1%. Across clinics, the average proportion of patients qualifying for VFC was 43%, and non‐White patients were 14.1%. The mean rate of HPV vaccine ≥1 dose was lower among rural clinics (46.9% vs 51.1%, P = .039), as was vaccination UTD (40.5% vs 49.9%, P < .001). Adjusting for differences in individual‐ and clinic‐level characteristics, rural disparities were no longer statistically significant. Conclusions: Both individual‐ and clinic‐level characteristics play a role in rural disparities in HPV vaccination, and modifiable clinic‐level differences may be opportune targets to address these disparities.